BETWEEN DIAGNOSIS AND ACTION: PEDAGOGICAL COORDINATORS' COGNITIONS ABOUT THE AVALIA MT SYSTEM IN TEACHING AND LEARNING (REMUNOM, 2025)
The article analyzes the cognitions of pedagogical coordinators regarding the impact of the Avalia MT System assessments on teaching and learning. External assessments, conceived as instruments for diagnosis and pedagogical planning, play a central role in defining teaching strategies. The aim of the study was to understand the perceptions of coordinators from state public schools about the contribution of these assessments to identifying learning gaps and supporting pedagogical replanning. This qualitative research, with a descriptive and phenomenological approach, was conducted with four pedagogical coordinators from state schools in Mato Grosso, whose professional experience ranged from 4 to 12 years. Data collection was carried out through questionnaires using a Likert scale, in which participants evaluated 11 statements about the impact of the assessments on their pedagogical practices. Statistical analysis of the responses revealed a predominantly positive perception regarding the usefulness of these assessments for diagnosing learning and planning pedagogical actions. The results indicate that Avalia MT has proven effective for pedagogical replanning, especially in recovering unconsolidated content. However, there is a need for greater integration between assessment data and everyday pedagogical practices. Furthermore, it is suggested that continuous support be provided to teachers in order to enhance the use of assessment results in the teaching and learning process.